ANALYSIS OF THE FREE CARBON CONTENT IN THE SYNTHESIS OF CALCIUM CYANAMIDE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Technical solutions have been developed to create a technology for the production of calcium cyanamide from lime, carbonate anhydride and industrial ammonia. A technological scheme for the production of nitrogen fertilizer and an effective defoliant - calcium cyanamide was developed and the optimal technological parameters of the process were determined at the experimental plant. An experimental batch of calcium cyanamide was produced.